17-beta estradiol inhibits oxidative stress-induced accumulation of AIF into nucleolus and PARP1-dependent cell death via estrogen receptor alpha. Issue 1 (5th January 2015) - Batnasan, Enkhzaya; Wang, Ruoxi; Wen, Jitao; Ke, Yueshuang; Li, Xiaoxue; Bohio, Ameer Ali; Zeng, Xianlu; Huo, Hongliang; Han, Liping; Boldogh, Istvan; Ba, Xueqing
Highlights Estrogen inhibits H2O2-induced PARP1 activation and nuclear fragmentation. Estrogen blocks H2O2-induced AIF translocation to nucleoli. Estrogen protects MCF-7 cells from H2O2-induced cell death. Estrogen receptor alpha mediates the protective role of estrogen.